Reemergence of superconductivity by 4d transition-metal Pd doping in over-doped 112-type iron pnictide superconductors Ca0.755La0.245FeAs2. (10th September 2019) - Xing, Xiangzhuo; Li, Zhanfeng; Veshchunov, Ivan; Yi, Xiaolei; Meng, Yan; Li, Meng; Lin, Bencheng; Tamegai, Tsuyoshi; Shi, Zhixiang
Abstract: In 112-type iron-based superconductors (IBSs), rare earth (e.g. La) doping enhanced antiferromagnetic (AFM) order and 3 d transition-metal (e.g. Co, Ni) doping induced reemergence of superconductivity (SC) in the over-doped regime (non-SC) are of particular interest, providing a significant opportunity to further understand the relationship between SC and AFM order in IBSs. Recently, 4 d transition-metal Pd-doped 112-type Ca1- y La y Fe1- x Pd x As2 ( x > 0.2, 0 ≤ y ≤ 0.3) compounds, which crystallized in new orthorhombic and tetragonal structures, have been identified ( Inorg. Chem. 56 3030 (2017)). However, none of them exhibit SC, probably due to the oversubstitution of Pd for Fe. Here, to reveal the impact of slight Pd doping on the over-doped Ca1- y La y FeAs2 and compare to 3 d Co/Ni doping series, single crystals of Ca0.755 La0.245 Fe1- x Pd x As2 with 0 ≤ x ≤ 0.08 are successfully grown using the self-flux method. We find that, upon only a small amount of Pd doping ( x = 0.013), bulk SC with a maximum T c of 28.5 K is reemerged, in contrast to the case with high Pd doping level. Moreover, based on the electrical resistivity and magnetization data, we construct the temperature-composition ( T – x ) phase diagram, the shape of which, particularly for the region where the AFM and SC phases coexist microscopically, is almost identical to that of Ca0.76 La0.24 Fe1- x Ni x As2, but is distinctly different from that of Ca0.74 La0.26 Fe1- x Co x As2, presumably due to the presence of complex doping mechanism in 112-type IBSs. Finally, for one selected single crystal with x = 0.013, superconducting properties including critical current density, vortex pinning mechanism, and vortex diagram are systematically studied by magnetization, magneto-optical imaging, and magneto-resistivity measurements. Our work provided more insight into the phase diagrams and superconducting properties of 112-type IBSs, allowing better understanding of its superconducting mechanism and developing the potential applications.